Economics in minutes - Kishtainy, Niall (London : London : Quercus, 2014)
"The quickest possible way to learn about the principles of economics, from supply and demand to financial bubbles and fair trade"--Page 4 of cover.
Introduction -- Markets, efficiency, and fairness -- Money and finance -- Firms and industry -- Income, unemployment, and inflation -- Economic policy and the government -- The international economy -- Society and the economy -- Growth and development -- Glossary.
Introduction -- Markets, efficiency, and fairness -- Money and finance -- Firms and industry -- Income, unemployment, and inflation -- Economic policy and the government -- The international economy -- Society and the economy -- Growth and development -- Glossary.
"200 key concepts explained in an instant"--Cover.
Includes index.
Keywords: Economics; Economics -- History; Economics; economics; Economics; History